PENGUJIAN POTENSI ALERGENITAS COAT PROTEIN OF SUGARCANE MOZAIC VIRUS PADA TANAMAN TEBU TRANSGENIK - Avif Firdausy Septian; Intan Ria Neliana; Banun Kusumawardani; Bambang Sugiharto (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2021)
Sugarcane resistant to sugarcane mosaic virus (SCMV) was developed by overexpression of gene for coat protein (CP). Therefore, this study aimed at investigating the potential allergenicity of CP-SCMV in transgenic sugarcane. Allergenicity was assessed by analysis in silico and in vitro. In silico analysis using AllergenOnline FASTA alignment of full-length CP-SCMV amino acid showed that the protein had no similarity with allergen protein. However, the alignment using 80 mer CP-SCMV showed over 35% similarity, but this result was considered as false positive. In silico analysis on digestion capability of protease found the cutting sites of CP-SCMV by pepsin, trypsin and chymotrypsin. This result was further confirmed by in vitro gastrointestinal digestion in that CP-SCMV was digested by pepsin and trypsin. Although CP-SCMV was less degraded by in vitro heat treatment and quantitatively underwent slight decrease after 30-minute heating on 90 ºC, the protein might lose its function. These results indicated that CP-SCMV was considered having no potential allergen in transgenic sugarcane resistant to SCMV. Tebu tahan sugarcane mosaic virus (SCMV) dirakit melalui overekspresi gen untuk coat protein (CP). Oleh karena itu, penelitian ini bertujuan menguji alergenitas CP-SCMV pada tebu transgenik. Pengujian alergenitas dilakukan melalui analisis in silico dan in vitro. Hasil analisis in silico dengan pensejajaran AllergenOnline FASTA full-length asam amino CP-SCMV menunjukkan tidak ada kesamaan dengan protein alergen. Namun demikian pada pensejajaran 80 mer, CP-SCMV mempunyai kemiripan di atas 35% dengan alergen, tetapi hasil ini memiliki kecenderungan positif palsu. Analisis in silico terhadap kemampuan cerna protease ditemukan adanya sisi pemotongan CP-SCMV oleh enzim pensin, trypsin dan chymotrypsin. Hasil ini dikonfirmasi lebih lanjut dengan analisis in vitro pencernaan gastrointestinal yang menunjukkan bahwa CP-SCMV terdegradasi oleh pepsin dan trypsin. Walaupun hasil analisis in vitro menunjukkan CP-SCMV kurang dipengaruhi oleh perlakuan panas dan hanya sedikit berkurang pada pemanasan 90 ºC selama 30 menit, tetapi mungkin fungsi protein telah rusak. Hasil penelitian ini menyimpulkan bahwa CP-SCMV pada tanaman tebu transgenik tahan virus tidak berpotensi sebagai alergen.